Efisiensi Pemasaran Cabai Rawit Hiyung Di Kecamatan Tapin Tengah Kabupaten Tapin-Kalimantan Selatan - Yusuf Azis; Emy Rahmawati; A.Yousuf Kurniawan (University of Islam Malang, 2021)
The purpose of this study is to determine the marketing of Hiyung cayenne pepper, calculate the share price, cost, margin, and profit earned by producers/farmers and each marketing agency, and examine the level of marketing efficiency of Hiyung cayenne pepper. This study took place in the Tapin Tengah Subdistrict of the Tapin Regency of South Kalimantan Province. The Snowball Sampling approach was used to pick merchant responses. Primary and secondary data are both required. The findings revealed that Hiyung's cayenne pepper marketing channel is divided into two sections: Channel IA (Farmers – Collector Traders – Retailers at the Keraton Market – Consumers), Channel B (Farmers – Collecting Traders – Retailers at Binuang Market – Consumers), and Channel II (Farmers at the Binuang Market – Consumers). - Wholesalers – Collecting Merchants). The greatest marketing cost is Rp. 2,834,39/kg in channel II, and the lowest cost is Rp. 1,967,80 in channel IA with the marketing area in the Keraton market. In channel II, the highest margin is Rp.13,500,00./kg. Meanwhile, the smallest margin, Rp. 4,000.00/kg, is found in channel IA at the Keraton Market Retailer level. The highest marketing profit in channel II is Rp. 17,678.00/kg, whereas the highest profit is Rp. 7,999,46 in channel IA in the Keraton Market area. Channel IA Pasar Keraton has the highest percentage of farmers at 77.44 percent, while channel II has the lowest percentage of farmers at 62.59 percent. The largest profit share for wholesalers is 37.00 percent in channel II, while the lowest is 22.56 percent in channel 1 in the Keraton Market region. The most efficient marketing channel is channel IA, which serves the Keraton market. Its economic efficiency is superior to that of channels IB and II, and its technical efficiency is superior to that of the Keraton market. This translates to lower distribution costs and more acceptability by major institutions.